Service provider perceptions of transitioning from audio to video capability in a telehealth system: a qualitative evaluation - Robyn Clay-Williams; Melissa Baysari; Natalie Taylor; Dianne Zalitis; Andrew Georgiou; Maureen Robinson; Jeffrey Braithwaite; Johanna Westbrook (BMC, 2017)
Abstract Background Telephone consultation and triage services are increasingly being used to deliver health advice. Availability of high speed internet services in remote areas allows healthcare providers to move from telephone to video telehealth services. Current approaches for assessing video services have limitations. This study aimed to identify the challenges for service providers associated with transitioning from audio to video technology. Methods Using a mixed-method, qualitative approach, we observed training of service providers who were required to switch from telephone to video, and conducted pre- and post-training interviews with 15 service providers and their trainers on the challenges associated with transitioning to video. Two full days of simulation training were observed. Data were transcribed and analysed using an inductive approach; a modified constant comparative method was employed to identify common themes. Results We found three broad categories of issues likely to affect implementation of the video service: social, professional, and technical. Within these categories, eight sub-themes were identified; they were: enhanced delivery of the health service, improved health advice for people living in remote areas, safety concerns, professional risks, poor uptake of video service, system design issues, use of simulation for system testing, and use of simulation for system training. Conclusions This study identified a number of unexpected potential barriers to successful transition from telephone to the video system. Most prominent were technical and training issues, and personal safety concerns about transitioning from telephone to video media. Addressing identified issues prior to implementation of a new video telehealth system is likely to improve effectiveness and uptake.